Analysis for financial management - Higgins, Robert C. (Irwin, 1992)
Financial analysis is one of the most important and valuable skills for today's managers and executives. It is essential that you understand the impact on your organization's financial performance of every decision you make. Higgins gives you the essential tools, strategies, and tactics for improving the financial dimensions of your operating decisions. This completely revised Third Edition for Analysis for Financial Management covers recent developments in the finance field such as market signaling, market efficiency, and capital asset pricing and, for the first time, integrates international topics throughout the book. In addition to more traditional subjects, you'll find the facts on how to assess the performance of international subsidiaries, compare interest rates across different currencies, and manage foreign exchange exposure.